Characteristics of suicide-related crashes and their potential interventions: A literature review. (4th July 2022) - Imants, P.; Goodsell, R.S.; Chevalier, A.
Abstract: Objective: To develop countermeasures to decrease road trauma, it is essential to increase our understanding of fatal and injury crashes with suicidal intent. As suicide-related crashes can be difficult to identify it seems likely suicide-related road fatalities and injuries are under-reported. Under-reported crashes may lead to two policy issues: these types of casualty crashes may not receive adequate funding for countermeasure development and implementation due to not having a sufficient evidence-basis to justify allocation of resources, and may be miscategorized as having other factors contributing to the crashes, thus resources may be incorrectly allocated to countermeasures to address these other factors. This paper seeks to develop and document characteristics and potential countermeasures to identify and prevent such crashes. Methods: Two literature reviews of peer-reviewed journal manuscripts were performed to identify suicide-crash characteristics and potential countermeasures and strategies. Of 61 peer-reviewed journal manuscripts identified from the literature searches, 17 manuscripts fit the criteria and were reviewed. Information regarding the characteristics of suicide-related crashes, as well as potential strategies and countermeasures were gleaned from these manuscripts. Results: A list of characteristics was developed, underpinning development of a methodology to identify these types of crashes. Strategies and countermeasures recommended by international (road-) agencies to identify and prevent suicide-related crashes were documented and discussed. Conclusion: As suicide-related crashes almost always take place in public space, the grief and pain resulting from such crashes not only relates to the victim, the people who knew the victim, but in many cases also involve the general public. It is therefore paramount to start the discussion about suicide-related crashes to increase awareness, increase willingness to establish a reliable data and knowledge base, and encourage help seeking in individuals at increased risk of attempting suicide using this method.